Effect of Different Dietary Oils and Fat on Body Weight, Food Intake, Some Haematological and Biochemical Parameters in Female Albino Rats - Sadiq Abdullah, Zerawan; Yaseen Rasoul, Mohammed; Mohammed Shareef Mahmood, Nazar (Kurdistan Journal of Applied Research, 2018)
The present study investigates the influence of different dietary plant oils included sunflower oil (SO), olive oil (OO) corn oil (CO), and animal (AF) on different parameters in female albino rats. Twenty-two animals were divided equally and randomly into five groups, the treatment was performed by needle gavage. First group fed on basal diet and served as control. Second group fed on a basal diet with 0.3ml/rat animal fat orally. Third group fed on a basal diet with 0.3ml/rat sunflower oil orally. Fourth group fed on a basal diet with 0.3ml/rat olive oil orally. Fifth group fed on a basal diet with 0.3ml/rat corn oil orally. It continued for 28 days. Several parameters were measured during and after the study such as body weight, food intake, organ weight (kidney, liver and spleen) Haematological parameters (Hb, RBC, WBC, PLT, HCT and MCV), lipid profile (Total cholesterol, TG, HDL and LDL). Commonly plant oils and animal fat showed both benefits and harmful effects on the mentioned parameters; the corn oil and olive oil played important role through generating the healthy signs among other oils and animal fat. The present results concluded that both corn oil and olive oil may own positive effect than the other animal fat sunflower oil of people used in their daily diet.